Review Article: Characteristics of Ovarian Cancer Across Age, Epithelial Histopathology, and Stages - Subhika Laksmi; Riza Rivany; Deri Edianto; Denny Rifsal Siregar (Sumatera Medical Journal, 2024)
Background: Ovarian cancer is a disease that has a high mortality rate, it has 185 thousand deaths in 2018. In Indonesia, it is estimated that there are 100 cancer patients per 100 thousand people. Ovarian cancer is a malignancy with no specific symptoms, as a result advanced stage is commonly found at diagnosis and there is no effective screening test to date. However, genetic factors have been found to play a role in this disease. Objective: The aim of this study is to find out the characteristics of ovarian cancer patients. Methods: This research uses a review article research design, with a narrative type. Data collection was taken from a collection of journals sourced from Pubmed and met the inclusion and exclusion criteria set by the author and then summarized. Six journals that included the characteristics of  ovarian cancer patients are included in this review article. Results: According to the six journals, the mean age is 54 years old, the most stage found is stage 3, and the most epithelial histopathology found is serous. Conclusion: According to the six journals that were reviewed, the characteristics of ovarian cancer patients based on age, stage, and epithelial histopathology were found to be consistent with the theory that has been established.